Plasmodesmata-Dependent Intercellular Movement of Bacterial Effectors - Li, Zhongpeng; Variz, Haris; Chen, Yani; Liu, Su-Ling; Aung, Kyaw (Frontiers in Plant Science, 2021)
Pathogenic microorganisms deliver protein effectors into host cells to suppress host immune responses. Recent findings reveal that phytopathogens manipulate the function of plant cell-to-cell communication channels known as plasmodesmata (PD) to promote diseases. Several bacterial and filamentous pathogen effectors have been shown to regulate PD in their host cells. A few effectors of filamentous pathogens have been reported to move from the infected cells to neighboring plant cells through PD; however, it is unclear whether bacterial effectors can traffic through PD in plants. In this study, we determined the intercellular movement of Pseudomonas syringae pv. tomato (Pst) DC3000 effectors between adjoining plant cells in Nicotiana benthamiana. We observed that at least 16 Pst DC3000 effectors have the capacity to move from transformed cells to the surrounding plant cells. The movement of the effectors is largely dependent on their molecular weights. The expression of PD regulators, Arabidopsis PD-located protein PDLP5 and PDLP7, leads to PD closure and inhibits the PD-dependent movement of a bacterial effector in N. benthamiana. Similarly, a 22-amino acid peptide of bacterial flagellin (flg22) treatment induces PD closure and suppresses the movement of a bacterial effector in N. benthamiana. Among the mobile effectors, HopAF1 and HopA1 are localized to the plasma membrane (PM) in plant cells. Interestingly, the PM association of HopAF1 does not negatively affect the PD-dependent movement. Together, our findings demonstrate that bacterial effectors are able to move intercellularly through PD in plants.